Distribution Characteristics and Ecological Risk Assessment of Organophosphate Esters in Surface Soils of China - Guorui Zhou; Yizhang Zhang; Ziye Wang; Mingrui Li; Haiming Li; Chen Shen (Toxics)
The chemical flame retardants represented by organophosphate esters (OPEs) are widely used and have a serious impact on the environment. In this study, we collected data on the exposure levels of ten OPEs in Chinese soils in recent years and performed an ecological risk assessment. The results showed that the levels of OPEs varied considerably throughout different regions of China, with high exposure levels in highly urbanized or industrialized areas such as Guangdong Province and Northeast China, where the mean value was >200 ng/g. The content of OPEs in the soil in industrial and commercial areas was significantly higher than in other regions, indicating that the concentration of OPEs in the soil is closely related to local economic development and the degree of industrialization. Meanwhile, the number of studies reporting on OPEs and their exposure concentrations have increased significantly since 2018. Through the ecological risk assessment, it was found that TCP, EHDPP and TEHP pose high ecological risks. Although some OPEs, such as TCIPP, have low ecological risk levels overall, their high exposure concentrations are still worthy of attention. This study details the general status of OPE contamination in Chinese soils, which can serve as a reference for ecological environmental supervision.